Legal Accountability for Environmental Impacts Resulting from the Use of Tear Gas in Public Demonstrations - Maghfiroh, Laily (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the form of legal liability for environmental pollution caused by the use of tear gas during the demonstration on August 28–29, 2025, in Jakarta, as well as to examine the environmental impacts resulting from the use of such chemical agents. The research employs a normative juridical method using statutory, conceptual, and case approaches. The legal materials consist of primary sources, including the 1945 Constitution of the Republic of Indonesia, Law Number 32 of 2009 on Environmental Protection and Management, and various relevant police regulations, supported by secondary and tertiary legal materials. The analysis is conducted through a descriptive qualitative approach, comparing the empirical reality of tear gas use that leads to pollution and public health impacts with the legal norms that should guide law enforcement officials in accordance with environmental law principles and human rights standards. The findings indicate that the use of tear gas in crowd control activities has the potential to violate environmental law provisions, cause air pollution, and negatively affect public health and the ecological balance in the affected areas.